Development and Validation of a Simultaneous HPLC Method for Quantification of Atenolol and Amlodipine Besylate in Tablet Form (International Journal of Scientific Research in Science and Technology, 2026)
A Reverse phase method has been developed for the quantitative estimation of Atenolol and Amlodipine Besylate in Tablets. The Quantification was carried out using RP stainless steel column ODS C18 250 x 4.6 x 5 μ L1 packing in Isocratic mode with mobile phase containing 0.03 M potassium buffer: Acetonitrile in the ratio of 50:50 Adjust pH3.5 with ortho-phosphoric acid. Degas this solution before use. Flow rate 1.0 ml/minute and the detection wavelength was set at 237 nm and the linearity was found to be in the range of 16-22 ug/ml for Atenolol and 8 to 12 ug/ml for Amlodipine Besylate. The proposed method was found to be simple, precise, accurate, reproducible for the Estimation of Atenolol and Amlodipine Besylate.